The puzzle box : a novel [large type] - Trussoni, Danielle ([Mike Brink], 2025)
"It is the Year of the Wood Dragon, and the ingenious Mike Brink has been invited to Tokyo, Japan, to open the legendary Dragon Box. The box was constructed during one of Japan's most tumultuous periods, when the samurai class was disbanded and the shogun lost power. In this moment of crisis, Emperor Meiji locked a priceless Imperial secret in the Dragon Box. Only two people knew how to open the box--Meiji and the box's sadistic constructor--and both died without telling a soul what was inside or how to open it. But Brink is not just any puzzle master. He may be the only person alive who can crack it. His determination is matched only by that of two sisters, descendants of an illustrious samurai clan, who will stop at nothing to claim the treasure. Brink's quest launches him on a breakneck adventure across Japan, from the Imperial Palace in Tokyo to the pristine forests of Hakone to an ancient cave in Kyushu. In the process, he discovers the power of Meiji's hidden treasure, and more crucially the true nature of his extraordinary talent."--